Hypoxia in Bone and Oxygen Releasing Biomaterials in Fracture Treatments Using Mesenchymal Stem Cell Therapy: A Review - Teh, Seoh Wei; Koh, Avin Ee-Hwan; Tong, Jia Bei; Wu, Xiaoyun; Samrot, Antony V.; Rampal, Sanjiv; Mok, Pooi Ling; Subbiah, Suresh Kumar (Frontiers in Cell and Developmental Biology, 2021)
Bone fracture cases are commonly presented in varying degrees of severity, and is usually a manifest of direct physical injury or bone-related diseases such as osteoporosis. Although the bone is seen as a rigid structure, it is classified as a connective tissue that constantly remodels itself throughout a human’s lifespan in a highly vascularized environment. Despite having modest regenerative potential, especially in children, a loss of blood supply in the bone can impede cellular repair and potentially lead to osteonecrosis. This pathophysiology is commonly observed in the neck of femur, scaphoid, and talus bone. In recent years, mesenchymal stem cell (MSC) therapy have been used to aid in the regeneration of bone afflicted. However, the cut-off in blood supply due to bone fractures can lead to hypoxia-induced changes in engrafted MSCs. Researchers have designed several oxygen generating biomaterials and yielded varying degrees of success in enhancing tissue salvage and preserving cellular metabolism under ischemia. These can be utilized to further improve stem cell therapy for bone repair. In this review, we touch on the pathophysiology of these bone fractures and review the application of oxygen generating biomaterials to further enhance MSC-mediated repair of fractures in the three aforementioned parts of the bone.